Ambienti digitali per l'educazione all'arte e al patrimonio - Luigini, Alessandro (Educazione al patrimonio culturale e formazione dei saperi - Open Access, 2018)
The book collects the contributions of scholars from disciplines of education and digital representation to jointly investigate the lines of development of education to art and heritage. Pedagogical knowledge brought into digital environments, both Augmented Reality and Immersive Virtual Reality, enhances its effectiveness in the signification of an educational experience whose main objectives seem to be art in all its forms and cultural heritage in all its expressions.